2018
DOI: 10.1002/cpdd.447
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the Cardiac Safety of PGFReceptor Antagonist OBE022 in a First‐in‐Human Study in Healthy Subjects, Using Intensive ECG Assessments

Abstract: OBE022, a new orally active prostaglandin F2α receptor antagonist (OBE022) with myometrial selectivity is being developed to reduce uterine contractions during preterm labor. This first‐in‐human study evaluated the effect of OBE022 following multiple doses on the QT interval in 23 healthy postmenopausal women, using the effect of a meal on QTc to demonstrate assay sensitivity. We report the cardiac safety outcome performed during the multiple ascending part of this trial. OBE022 was administered after a standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
(73 reference statements)
1
13
0
Order By: Relevance
“…The QTc shortening after a meal was previously proposed to be a result of the net effect of the antagonistic effects exerted by C‐peptide and glucose . This and other published studies confirm that the QT interval shortening in response to standardized meals is reproducible and independent of time of day . The marked effect on HR and the inverse relation between HR and QTcF has been previously reported after food intake …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The QTc shortening after a meal was previously proposed to be a result of the net effect of the antagonistic effects exerted by C‐peptide and glucose . This and other published studies confirm that the QT interval shortening in response to standardized meals is reproducible and independent of time of day . The marked effect on HR and the inverse relation between HR and QTcF has been previously reported after food intake …”
Section: Discussionsupporting
confidence: 81%
“…43 This and other published studies confirm that the QT interval shortening in response to standardized meals is reproducible and independent of time of day. 44 The marked effect on HR and the inverse relation between HR and QTcF has been previously reported after food intake. 13 Of note was the short-lasting peak in HR values during the 3 to 4 hours after dose, which corresponds to the end of bed rest required for after-dose study assessments ( Figure 3B) and most volunteers would have left their beds for physical mobilization.…”
Section: Discussionmentioning
confidence: 71%
“…All subjects fasted for at least 10 h predose and 4 h postdose. Venous blood samples were collected for PK analysis predose and 0.25, 0.5, 0.75, 1, 1.5, 2, 2.5, 3, 3.5, 4, 6,7,8,12,16,24,36,48,72,96,120 and 144 h postdose.…”
Section: Part A: Sadsmentioning
confidence: 99%
“…OBE022 is a potent, small molecule PGF2α receptor antagonist being developed to inhibit preterm labour . Ongoing clinical investigations are testing twice daily administrations of OBE022 during up to 7 days in preterm labour patients.…”
Section: Introductionmentioning
confidence: 99%
“…It was important to first conduct trials in healthy nonpregnant female volunteers rather than preterm labour patients as it was important to determine the safety and tolerability of OBE022 when coadministered with various standard of care medications. Data from the FIH trial demonstrated that OBE022 would not expose them to an increased risk …”
Section: Introductionmentioning
confidence: 99%